Comparison of visual performance of toric versus non-toric intraocular lenses with same material - Yamauchi T (Dove Medical Press, 2018)
Tomofusa Yamauchi,1 Hitoshi Tabuchi,1 Kosuke Takase,1 Zaigen Ohara,1 Hitoshi Imamura,1 Yoshiaki Kiuchi2 1Department of Ophthalmology, Tsukazaki Hospital, Himeji, Japan; 2Department of Ophthalmology, Hiroshima University, Hiroshima, Japan Aim: We compared the visual performance of toric intraocular lenses (IOLs) and non-toric IOLs made of the same material.Patients and materials: The subjects included patients implanted with either Acrysof IQ® toric IOLs (SN6AT3-9) or Acrysof IQ® IOLs (SN60WF) bilaterally. The toric group included 103 patients who were implanted with Acrysof IQ toric IOLs bilaterally. The non-toric group was a corneal astigmatism-matched control group and included 103 patients who were implanted with Acrysof IQ IOLs bilaterally.Results: The uncorrected distance visual acuity was significantly better in the toric group, whereas the uncorrected 50 cm visual acuity was better in the non-toric group. There was no significant difference in contrast sensitivity (with and without glare) between both the groups. The rate of spectacle dependency for distance vision was significantly lower in the toric group. There were no significant differences between the two groups in all items of the postoperative quality-of-vision questionnaire (25-item Visual Function Questionnaire).Conclusion: The toric IOLs used in this study reduced spectacle dependency more than the non-toric IOLs and did not compromise the subjective visual function, but the uncorrected 50 cm vision was worse in toric IOL implanted eyes. Keywords: cataract, cataract surgery, astigmatism, visual function